2020
DOI: 10.1002/jso.26154
|View full text |Cite
|
Sign up to set email alerts
|

Is minimally invasive surgery of lesions in the right superior segments of the liver justified? A multi‐institutional study of 245 patients

Abstract: Background: Controversy exists regarding the safety and feasibility of minimally invasive resection for lesions in segments 7 or 8. We compare outcomes of minimally invasive surgery (MIS) and Open parenchymal sparing liver resections at two high-volume centers. Methods: From 2003 to 2016 we identified patients who underwent MIS or Open resections for lesions in segments 7 or 8 at two institutions (MSKCC and SGH). Outcomes were compared using univariate and multivariate analyses. Results: Two-hundred and forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In this study, 41% of the MIS cases were located in the difficult posterosuperior segments 2 . Nonetheless, we, like many other authors, have previously demonstrated that patients benefit from the same advantages of MIS over the open approach even for tumors in in these difficult locations 6 …”
supporting
confidence: 64%
“…In this study, 41% of the MIS cases were located in the difficult posterosuperior segments 2 . Nonetheless, we, like many other authors, have previously demonstrated that patients benefit from the same advantages of MIS over the open approach even for tumors in in these difficult locations 6 …”
supporting
confidence: 64%
“…In addition, most well‐validated difficulty scoring systems for MILR grade CH and RAS as ‘highly difficult’ procedures that should only be attempted by experienced hepatobiliary surgeons in a tertiary referral centre 13,45 . With regards to the discussion of technically difficult MILR, our institution recently reported on the oncological safety and benefits of a minimally invasive approach to segments VII and VIII lesions, including decreased blood loss and shorter duration of hospital stay 46 …”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]14 These challenges may be partially overcome by using the lateral position, additional intercostal trocars, and the flexible tip laparoscope. [6][7][8][15][16][17] Nonetheless, despite the greater complexity, LLR of segments 7 and 8 have shown the known advantages of minimally invasive surgery over the open approach such as significantly lower blood loss and length of hospital stay. 15,18 To date, there are no head-to-head comparative studies between LLR of Segments 7 and 8.…”
Section: Discussionmentioning
confidence: 99%